2015
DOI: 10.1111/papt.12076
|View full text |Cite
|
Sign up to set email alerts
|

Transition to motherhood in women with eating disorders: A qualitative study

Abstract: Eating disorders (EDs) are known to seriously affect fertility, pregnancy, and pregnancy outcomes. Our research sheds a light on experiences of pregnancy in women with ED and ultimately helps to define a window for intervention. Our findings have important implications in understanding mechanisms of relapse in the post-partum period and consequently could help in tailoring an adequate intervention for women with ED and in preventing ED relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 65 publications
1
28
2
Order By: Relevance
“…We are also unable to identify specific diagnostic procedures, or treatment types. A strength of this study is our ability to establish time order by identifying ED diagnosis before first fertility event, however EDs are often experienced concurrently with first and later pregnancies (Cardwell, 2013; Taborelli et al, 2016; Ward, 2008). Future research could build on our study by examining how ED onset and relapse, treatment timing, and ED co-occurrence with pregnancy may influence long-term reproductive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We are also unable to identify specific diagnostic procedures, or treatment types. A strength of this study is our ability to establish time order by identifying ED diagnosis before first fertility event, however EDs are often experienced concurrently with first and later pregnancies (Cardwell, 2013; Taborelli et al, 2016; Ward, 2008). Future research could build on our study by examining how ED onset and relapse, treatment timing, and ED co-occurrence with pregnancy may influence long-term reproductive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The parental diagnosis of an eating disorder (ED) has been suggested to be an important factor in child development, and it may play a crucial role in shaping offspring's mental health, particularly in early childhood (Micali, Stahl, Treasure, & Simonof, ; Stein, Woolley, Cooper, Winterbottom, Fairburn, & Cortina‐Borja, ). To date, most empirical and clinical studies of parental EDs have used ecological theories (Bronfenbrenner, , ; Sameroff, ) to focus on the transgenerational transmission of anorexia and bulimia symptoms in an equifinality framework (de Barse et al., 2015; Cerniglia et al., ; Taborelli et al., ) by tracing their offspring's stability from childhood to adolescence and adulthood. These studies have found that the impact of parental EDs on their infants’ psychological profiles exceeded the transmission of ED psychopathology and led to an increased and complex risk for the onset of emotional and behavioral problems (Cimino, Cerniglia, Paciello, & Sinesi, ; Micali et al.…”
Section: Parental Eating Disorders and Outcomes On Their Offspring's mentioning
confidence: 99%
“…Parents are taught how to support change in the different stages (Treasure, Sepulveda, et al, 2007). The SUCCEAT intervention informs the parents that patients sometimes relapse and need to go through repeated cycles of the stages of change (Hibbs, Magill, et al, 2015;McKnight & Boughton, 2009;Taborelli et al, 2016). The different theoretical models combine intrapersonal and interpersonal factors, as well as knowledge and skills, that can help parents to manage their own reaction to the illness and to provide an environment that is conducive to change .…”
Section: Theoretical Background Of the Succeat Interventionmentioning
confidence: 99%